Transcriptomic and Non-Targeted Metabolomic Analyses Reveal the Flavonoid Biosynthesis Pathway in Auricularia cornea - Li Meng; Shaoyan Zhang; Xiaoran Bai; Xiaobo Li; Qingji Wang; Li Wang; Wei Wang; Zhuang Li (Molecules, 2022)
Flavonoids, which are abundant in plants, are recognized for their antioxidant and anticancer roles in clinical applications. However, little is known about the molecular basis of flavonoid biosynthesis in fungi. In this study, we found that inclusion of leachate of Korshinsk peashrub (Caragana korshinskii) in the fermentation medium increased the total flavonoid content of the edible fungus Auricularia cornea by 23.6% relative to that grown in a control medium. Combined transcriptomic and non-targeted metabolomic analysis of the flavonoid biosynthesis pathway in A. cornea illustrated that there are important metabolites in the phenylpropanoid, coumarin and isoflavonoid biosynthesis pathways. In addition, we found that certain homologous genes encode phenylalanine ammonia lyase (PAL), polyphenol oxidase (PPO) and chalcone isomerase (CHI) in these biosynthesis pathways. These results, in this study, provide a new line for studying the regulation of flavonoid production in edible fungi.